2003
DOI: 10.1149/1.1580151
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Analysis of IS of Polycrystalline Materials with Blocking or Conducting Grain Boundaries: From Microcrystals to Nanocrystals

Abstract: Impedance spectra ͑IS͒ of a polycrystalline sample with macroscopic dimensions are analyzed based on the brick layer model with parallel and series grain boundaries ͑gb͒. The gb width is taken as 0.5 nm, in accordance with the classical Fisher model of gb diffusion. Three mean grain size values of 500, 50, and 5 nm are simulated, corresponding to a change from microcrystalline to nanocrystalline ceramics. A constant conductivity of the grain interior (10 Ϫ3 S/m͒ and of the series gb (10 Ϫ6 S/m͒ is assumed. Imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 17 publications
0
30
0
Order By: Relevance
“…This was first accomplished using the S-BLM [18], which is appropriate only in the case of relatively thin grain boundaries. In a theoretical analysis of nanocrystalline ceramics using the SP-BLM, Bouchet and co-workers [19] found that experimental determination of the electrical properties of nanocrystalline ceramics by impedance spectroscopy is complicated by the superposition of parallel and serial paths (see Fig. 1(a)).…”
Section: Resultsmentioning
confidence: 99%
“…This was first accomplished using the S-BLM [18], which is appropriate only in the case of relatively thin grain boundaries. In a theoretical analysis of nanocrystalline ceramics using the SP-BLM, Bouchet and co-workers [19] found that experimental determination of the electrical properties of nanocrystalline ceramics by impedance spectroscopy is complicated by the superposition of parallel and serial paths (see Fig. 1(a)).…”
Section: Resultsmentioning
confidence: 99%
“…In microcrystalline ceramics, where the effective grain boundary width is negligible compared to the grain size, the contribution of the parallel grain boundary can be neglected. However, parallel grain boundary contribution must be taken into account if the parallel grain boundary conductivity becomes significantly larger than that of the grain and/or if the effective grain boundary width is no longer negligible with respect to the grain size (Bouchet et al, 2003). The change in the grain boundary resistance with x could be explained by the change of the relative density as shown in Figure 7.…”
Section: Methodsmentioning
confidence: 99%
“…Their contributions to the total conductivity can then be determined based on geometric considerations [i.e., the bricklayer model (Verkerk et al, 1982)]. However, when grain boundaries are comparable to or more conductive than the bulk, the impedance spectra cannot be readily deconvoluted (Bouchet et al, 2003). At room temperature, the Nyquist plot of the LLZO cell consists of a partial semicircle at high frequency and a spike at low frequency.…”
Section: Scanning Electrochemical Microscopy Experimentsmentioning
confidence: 99%